Integrated performance measurement system in Small and Medium Enterprises: the role of leadership and decision-making style - Amizawati Mohd Amir; Sofiah Md Auzair; Zulaihan Ismail (Fakulti Ekonomi dan Pengurusan, 2014)
The purpose of this study is to observe the integrated performance measurement system (IPMS) based on the perspective of Small and Medium Enterprises (SMEs). Building on the upper echelons perspective, the study investigates the role of SME entrepreneurs/top management leadership in determining the implementation of IPMS to assist them in making decisions. IPMS is a useful managerial tool for measuring and improving the decision-making and control process among the SMEs. Our results, based on a survey administered to 90 SMEs, reveal that leadership style has no direct effect on the IPMS practice. Instead, the decision-making style mediates the relationship between the leadership style and IPMS. Regardless of the different leadership styles, we find that a comprehensive decision approach is the way of making decisions that emphasize the integration between financial and nonfinancial measures, and between internal and external factors.